Leadership skills in relation to library leaders key performance index / Kamariah Nor Mohd. Desa and Associate Professor Dr. Norliya Ahmad Kassim - Mohd. Desa, Kamariah Nor; Ahmad Kassim, Norliya (2011)
This paper discusses the concept of leadership skills for the Malaysian public university librarians at all levels for the library to retain its role as a repository of knowledge. Katz (1955) suggested a concept that an effective administration (i.e. leadership) depends on three basic personal skills: technical, human, and conceptual skills. The role of library leaders involves motivating and inspiring people to achieve the organizational objectives. With so many teams, and groups from different grades and positions in academic libraries involved in managing change, their roles as leaders are expected to increase. They have to collaboratively work, plan, implement, administer, and evaluate services and performance efficiently. In relation to Key Performance Index (KPIs) attainment, the roles of the librarians are to idealize the vision, mission, and objectives of the library. They are expected to be able to demonstrate their abilities to deliver and achieve the organizational goals. This paper also discusses the ways in developing effective leaders in relation to preparing for succession planning for future Chief Librarian.